Time dependent temperature effects on methane production in Arctic peat soils - Grunnvåg, Jeanette Slettnes (UiT Norges arktiske universitet, 2019)
Peatlands constitute the largest natural reservoir of carbon on the planet making them key components in the global carbon balance. Peatlands are mostly found in the northern hemisphere under cold conditions. As the world is warming and arctic peatlands are becoming heavily influenced by increasing temperatures, an increased interest in the peat soil microbial systems have arisen. Methane, a potent climate gas, is produced in the anaerobic environment of peatlands by methanogenic archaea which are supplied with carbon, energy and nutrients through a complex network of microbes. How these communities are influenced by changes in temperature is crucial for our understanding on the effects of climate change. In this master thesis the effect of gradually increasing temperatures on CH4 producing microorganisms in Arctic peat was studied within a seasonal timescale. The major aim was to provide a better understanding of how CH4 producing microorganisms in peat react to temperature changes over time. Multiple incubations were set up and gradually moved from 2°C to 9°C, through 3, 5 and 7.5°C. Throughout the incubations gas measurements and samples for chemical analysis were collected. Analysis of growth and enzyme activity was performed at the end of the experiment. Analyses of 16S rRNA genes were performed for samples at the start and end of incubation. Only small changes in the community composition were observed and no differences in the biomass between the start and end, or between temperature treatments. There was also no difference in the extracellular enzyme activity for the different temperature treatments. The CO2 production showed the same trend for all treatments throughout the experiment, while the CH4 production demonstrated a clear temperature dependence. Furthermore, using the Arrhenius equation it was shown that the temperature dependence of CH4 production rates as well as the growth rates for the whole community were comparable to that of pure culture of methanogens, but that the rates right after ...